Possibilities of Non-Destructive Testing Methods for Material Properties Determination - Křepelka, Jan (ECON Publishing, 2025)
This article focuses on the possibilities of using the pulse-echo method for determining material characteristics of concrete in structures. The subject of the performed experiment is to verify whether it is possible to estimate the elastic modulus on structures accessible from only one side , where the commonly used through-transmission method cannot be applied, and to compare it with this method. Additionally, it verifies how much the results differ between general and precise values for each tested location.
Keywords: Modulus of elasticity; concrete; pulse-echo; non-destructive testing